Effects of 2010–2045 climate change on ozone levels in China under a carbon neutrality scenario: key meteorological parameters and processes - L. Kang; H. Liao; K. Li; X. Yue; Y. Yang; Y. Wang (Atmospheric Chemistry and Physics)
We examined the effects of 2010–2045 climate change on ozone (O3) levels in China under a carbon neutrality scenario using the Global Change and Air Pollution version 2.0 (GCAP 2.0) model. In eastern China (EC), GCAP 2.0 and six other models from the Coupled Model Intercomparison Project Phase 6 (CMIP6) all projected increases in daily maximum 2 m temperature (T2max), surface incoming shortwave radiation (SW), and planet boundary layer height and decreases in relative humidity (RH) and sea level pressure. Future climate change is simulated by GCAP 2.0 to have large effects on O3 even under a carbon neutrality pathway, with summertime regional and seasonal mean maximum daily 8 h average (MDA8) O3 concentrations increasing by 2.3 ppbv (3.9 %) over EC, 4.7 ppbv (7.3 %) over the North China Plain, and 3.0 ppbv (5.1 %) over the Yangtze River Delta. Changes in key meteorological parameters were found to explain 58 %–76 % of the climate-driven MDA8 O3 changes over EC. The most important meteorological parameters in summer are T2max and SW in northern and central EC and RH in southern EC. Analysis showed net chemical production was the most important process that increases O3, accounting for 34.0 %–62.5 % of the sum of all processes within the boundary layer. We also quantified the uncertainties in climate-induced MDA8 O3 changes using CMIP6 multi-model projections of climate and a stepwise multiple linear regression model. GCAP 2.0 results are at the lower end of the climate-induced increases in MDA8 O3 from the multi-models. These results have important implications for policy-making regarding emission controls against the background of climate warming.